A construction methodology to share from qualitative research - Sánchez González, Marta Eugenia (2011)
This article summarized the methodological processlogical that I built during the investigation thatdeveloped in a freshman class I cycle during1999 and which was called "A New Look at the processes of reading and writing." The main objective of this study was to reveal aspects that promote or hinder innovation processes of reading and writingat that level of education and based in Costa Ricadesign proposals that information and update training to teachers and teachers.This qualitative research, ethnography wasassuming elements of case studies, hermeneutics and phenomenology.The construction of the methodology was fascinating, ahighly creative process. The back to school whereI completed my primary education, this time with a newLook, I got the opportunity to learn that school again. Learning space that gave me an opportunity to describe, analyze,interpret and construct meaning from practicesteaching that took place there.It was based on participant observation, in-depth interview and conversational interview, theanalysis of documents, photography and video inelaborated raw notes, then the notes cooked. Based on these records I designed several matrices that allowed me gradually, in a process of reflection and evaluation of information, organize the data in light of thequestions that guided the research. The organization of information guided me in developingthe five sections that give unity to the information gathered during the research process and findings allow for the achievement of the objective set.